THE CORRELATION BETWEEN FAMILY’S ECONOMIC SOCIAL WITH THE BUSINESS INTEREST IN BEAUTY (Journal of Technology and Operations Management, 2019)
This paper seeks to determine the relationship between socio-economic family and interest in entrepreneurship in the field of beauty at the Akademi Kesejahteraan Sosial Yogyakarta. This paper used correlation analysis approach to gather information from respondents. This study used a set of questionnaire to measure variables used in this study. Hypotheses were tested using non-parametric statistical methods to determine whether there is a relationship between socioeconomic family and interest in entrepreneurship in the field of beauty. The results showed that there was a significant relationship between socioeconomic family and interest in entrepreneurship with a moderate closure relationship of 0.371. Each variable in the results of data processing have a significant result in the interest of entrepreneurship with the result shown 27 (90%), and the socio-economic sector that has the largest entrepreneurial interest in income of 1 million-2.5 million (IDR) by 10 (33.3%). The results in the study of socioeconomic relations and interest in entrepreneurship were attracted by 15 (50%) and very interested in 12 (40%). This study has a significant result between socio-economic families with interest in entrepreneurship by reaching 90% of respondents surveyed turned out to have an interest in entrepreneurship. At low socioeconomic has greater entrepreneurial desire, someone at low socioeconomic family wants to improve their lives by entrepreneurship in one of the beauty procedures.